2021
DOI: 10.1186/s12884-021-04228-z
|View full text |Cite
|
Sign up to set email alerts
|

Placental pathology in a pregnant woman with severe COVID-19 and successful ECMO treatment: a case report

Abstract: Background Infection with SARS-CoV-2 during pregnancy can lead to a severe condition in the patient, which is challenging for obstetricians and anaesthesiologists. Upon severe COVID-19 and a lack of improvement after multidrug therapy and mechanical ventilation, extracorporeal membrane oxygenation (ECMO) is introduced as the last option. Such treatment is critical in women with very preterm pregnancy when each additional day of the intrauterine stay is vital for the survival of the newborn. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…A case report on the placenta of a symptomatic COVID-19 positive second-trimester pregnant mother with associated pre-eclampsia and placental abruption demonstrated the presence of high levels of SARS-CoV-2 in the STB of chorionic villi at the maternal-fetal interface under electron microscopy along with massive mononuclear cell infiltration (intervillositis) and fibrin deposits in the intervillous spaces. Immunohistochemical observations revealed CD68 and CD3 positive T lymphocytes [46]. The authors were the opinion that pre-eclampsia and coagulopathy were due to placental infection by SARS-CoV-2 (4).…”
Section: N Discussionmentioning
confidence: 92%
“…A case report on the placenta of a symptomatic COVID-19 positive second-trimester pregnant mother with associated pre-eclampsia and placental abruption demonstrated the presence of high levels of SARS-CoV-2 in the STB of chorionic villi at the maternal-fetal interface under electron microscopy along with massive mononuclear cell infiltration (intervillositis) and fibrin deposits in the intervillous spaces. Immunohistochemical observations revealed CD68 and CD3 positive T lymphocytes [46]. The authors were the opinion that pre-eclampsia and coagulopathy were due to placental infection by SARS-CoV-2 (4).…”
Section: N Discussionmentioning
confidence: 92%
“…A recent study analyzed the placentas of mothers who had suffered severe COVID-19 infection requiring ECMO. The authors found thrombosis in the basal plate’s spiral arteries, intramural endovascular trophoblasts in the third-trimester placentas, subchorionic hematoma, and chronic chorioamnionitis in the fetal membranes [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the studies decribing histological examination of placentas in the context of SARS-CoV-2 maternal infection (on Pubmed, with keywords “SARS-CoV-2” + “placenta” + “pathology”), which include three meta-analyses, poor fetal outcome has been frequently reported in association with the “placentitis triad”, consisting in intervillositis (with an acute or chronic infiltrate), excess fibrin deposition and trophoblastic necrosis [ Supplementary Table S1 ], refs. [ 3 , 4 , 5 , 6 , 8 , 9 , 10 , 12 , 13 , 14 , 15 , 16 , 17 , 20 , 21 , 22 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Table S1: Summary of the placental lesions in reported cases of SARS-CoV-2 infection in the literature [ 3 , 4 , 5 , 6 , 8 , 9 , 10 , 12 , 13 , 14 , 15 , 16 , 17 , 20 , 21 , 22 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
mentioning
confidence: 99%